THEORETICAL PROBLEMS OF THE FUNCTIONING OF PHRASEOLOGICAL UNITS - Ramina Djalolitdinovna Shukurova (Journal of Intellectual Property and Human Rights, 2023)
The study of the functioning of phraseological units in speech should be based on the achievements of linguists in the field of general theory of contextology. One of the tasks of linguistics is the possible complete representation of the semantics of any linguistic unit - from word to utterance - in all their semantic contextual connections, which eventually embrace the entire volume of the so-called polysemy of linguistic phenomena as a generalized category of real contextual manifestations.